The Use Of Discourse Markers To Improve Students’ Listening Skills In English Teaching Learning For Seventh Grade SMP Negeri 1 Mojotengah Wonosobo In 2023/2024 Academic Year - Yekti Nur Rahmawati; Sahid Sahid (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The skill of listening to the meaning and function behind speech is sometimes difficult for some people. This thesis analyzes discourse markers in the teaching and learning process using a discourse marker approach. The aim of this research is to determine the implementation of the listening learning model in improving student learning outcomes in each cycle, and to determine student learning motivation in class VII SMP Negeri 1 Mojotengah. The research method uses Classroom Action Research (PTK). The research is carried out in two cycles, each cycle consisting of planning, implementing actions, observing and reflecting. The subjects of this research are 32 students in class VII A of SMP Negeri 1 Mojotengah. The data collection uses in this research is quantative data. Quantative data takes the form of observation sheets, interviews, tests and documentation. The results obtained from this research include: 1) the application of the discourse model can improve students' listening skills, 2) student learning outcomes in each cycle have increased above the KKM, namely 75, after the discourse marker learning model was implemented. The average student learning outcome in the pre-cycle was 64 with a percentage of 53% (low), then cycle I obtained an average score of 71.88 with a presentation of 59% (medium), but it was still below standard so it continued in cycle II and experienced an increase with an average value of 88.75 with a percentage of 88% (high). This shows an increase from pre-cycle, cycle I, and cycle II.